Regulatory T cell microRNA expression changes in children with acute Kawasaki disease. (November 2014) - Ni, F.‐F.; Li, C.‐R.; Li, Q.; Xia, Y.; Wang, G.‐B.; Yang, J.
Summary Kawasaki disease (KD) is a type of systemic vasculitis syndrome related to immune dysfunction. Previous studies have implicated that dysfunctional regulatory T cells (Treg) may be associated with the immune dysfunction in KD. In the absence of microRNAs (miRNAs), forkhead box protein 3 (FoxP3)+ Treg develop but fail to maintain immune homeostasis. This study was designed to investigate the effects of miR‐155, miR‐21 and miR‐31 on Treg in children with KD. The proportions of CD4+CD25+FoxP3+ Treg and the mean fluorescence intensity (MFI) of phosphorylated‐signal transducer and activator of transcription (pSTAT)‐5 and pSTAT‐3 protein in CD4+CD25+ Treg were analysed by flow cytometry. The concentration of interleukin (IL)‐6 in plasma was measured by cytometric bead array. Real‐time polymerase chain reaction was performed to detect the levels of microRNAs and associated factors in CD4+CD25+ Treg. The proportion of Treg and the mRNA levels of the associated factors [FoxP3, glucocorticoid‐induced tumour necrosis factor‐receptor (GITR), cytotoxic T lymphocyte antigen (CTLA)‐4)] were significantly lower in KD patients (P < 0·05). MiR‐155 and miR‐21 levels were significantly down‐regulated and miR‐31 expression was higher in KD patients (P < 0·05). Plasma interleukin (IL)‐6 concentrations, pSTAT‐3 protein levels and suppressors of cytokine signalling (SOCS)‐1 mRNA expression were remarkably elevated in acute KD (P < 0·05), while pSTAT‐5 protein levels were remarkably decreased in acute KD (P < 0·05). These findings were reversed after intravenous immunoglobulin treatment (P < 0·05). Our results demonstrate that FoxP3 mRNA levels were primarily affected by the miR‐155/SOCS1 and the miR‐31 signalling pathways. These results suggest that the decrease in FoxP3+ Treg might be associated with decreased expression of miR‐155, leading to aberrant SOCS1/STAT‐5 signalling and overexpression of miR‐31 in patients with acute KD.